El θυμός en Eurípides y la peripecia trágica - Sousa, Ana Alexandra Alves de (2021)
Abstrat: The θυμός is a concept that comes from the Homeric poems, in which it characterizes the hero. In Euripides’ tragedies we see it associated with the change of tragic fate (περιπάθεια). The word is found in eleven plays: Medea, Heraclidae, Hippolytus, Hecuba, Supplicants, Heracles, Electra, Iphigenia among the Tauros, Phoenicians, Iphigenia in Aulis and Bacchae. In the tragedy Medea the concept is connected with the controversial infanticide. Our analysis associates the word with the essence of the Self, with its reasoning and with the impetus that changes the tragic destiny of characters like Jason, Hippolytus, Eteocles, Hecuba and Pentheus. The disturbing polysemy of the word will also lead us to love and marriage. The study of the contexts of θυμός in Medea will be very fruitful because, in this tragedy, we find all the complexity of the concept that the other dramatic works of Euripides prove. In truth, the poet used an epic word and wore it in tragic clothes.